(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
The media has ceased to be a passive channel transmitter of information and has become an active political participant, shaping the opinion and the democratic procedures. This review article explores the effects of both the traditional and the digital media on political communication in terms of agenda setting, framing, priming, and mediatization of politics. The paper relies on the latest empirical studies 2013-2025 to review how digital ecosystems and in particular, social media platforms and algorithm-based networks are transforming attitudes towards politics, electoral behaviour, civic engagement, and democratic participation. Inferences include a two-sided paradigm of media enhancing both access to political information, input and mobilization, and simultaneously heightening risks, such as misinformation, echo chambers, polarization, algorithmic influences and loss of institutional credibility. The paper contends that media effect is neither democratic nor anti-democratic; instead, media effect relies on platform architecture, regulatory, media literacy, or socio-political contexts. The paper underscores the significance of having an equal response by the institution, a mechanism of accountability, and civic education to protect the integrity of democracy without undermining the media-mediated participation and people’s communication.